Expression, purification and preliminary crystallographic analysis of the T6SS effector protein Tse3 from Pseudomonas aeruginosa. Issue 5 (22nd May 2013) - Lu, Defen; Shang, Guijun; Yu, Qian; Zhang, Heqiao; Zhao, Yanyu; Cang, Huaixing; Gu, Lichuan; Xu, Sujuan; Huang, Yan
<x xml:space="preserve">Abstract</x> Pseudomonas aeruginosa uses the type VI secretion system (T6SS) to inject effector proteins into rival cells in niche competition. Tse3, one of the effectors of T6SS, is delivered into the periplasm of recipient cells. Tse3 functions as a muramidase that degrades the β‐1, 4‐linkage between N‐acetylmuramic acid (MurNAc) and N‐acetylglucosamine (GlcNAc) in peptidoglycan, thus leading to lysis of the recipient cells and providing a competitive advantage to the donor cells. Here, the preliminary crystallographic study of Tse3 is reported. A crystal of Tse3 diffracted to 1.5 Å resolution. It belonged to space group C121, with unit‐cell parameters a = 166.99, b = 70.13, c = 41.94 Å, α = 90.00, β = 90.52, γ = 90.00° and one molecule per asymmetric unit.